THE TRANSLATION OF INFORMATION PATTERN FOR I CARE A LOT MOVIE SUBTITLE FROM ENGLISH TO INDONESIAN - Sajarwa, Sajarwa; Addinillah, Aulia; Mash’umah, Nadia Khumairo; Yanda, Cynthia; M. Al-maziidi, Ahmad Khalid (Lire Journal (Journal of Linguistics and Literature), 2021)
Movie subtitle translation is the transfer of meaning from source text into target text in the form of text under the screen with limited time and characters. One of the problems in translating movie subtitle is the information pattern. Information patterns are how the information is organized. This information arrangement includes information status and information urgency. This research uses descriptive and comparative methods. The results of the study indicate that (i) there are parallels in information pattern urgency, namely foreground position tends to be in the beginning of the speech; (ii) the misalignment of information status occurs in sentences translation with it subject and that impersonal and in interrogative and imperative sentences translation, as well as in sentences translation with the non-doer subject.